2017
DOI: 10.1007/s11011-017-0145-7
|View full text |Cite
|
Sign up to set email alerts
|

Resting regional brain metabolism in social anxiety disorder and the effect of moclobemide therapy

Abstract: While there is mounting evidence of abnormal reactivity of several brain regions in social anxiety disorder, and disrupted functional connectivity between these regions at rest, relatively little is known regarding resting regional neural activity in these structures, or how such activity is affected by pharmacotherapy. Using 2-deoxy-2-(F-18)fluoro-D-glucose positron emission tomography, we compared resting regional brain metabolism between SAD and healthy control groups; and in SAD participants before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…No imaging studies investigating regional activity at rest have reported differences that are statistically significant at stringent statistical thresholds (e.g., corrected for multiple comparisons; P , 0.05), suggesting that if such differences are present, they are probably small. At more liberal statistical thresholds, these studies provide evidence of disruptions in biologically plausible regions, including increases in several frontal regions, cerebellum (8), fusiform gyrus, and temporal pole (9) and decreases in subcallosal cortex and dorsal anterior cingulate cortex (10), as well as in pons, cerebellum, and precuneus (8). Investigating resting-state conditions using nuclear imaging with interregional correlations across subjects may be a more sensitive method to characterize abnormalities in SAD.…”
Section: Surrogates Of Neural Activity (Blood Flow Perfusion Metabomentioning
confidence: 87%
See 1 more Smart Citation
“…No imaging studies investigating regional activity at rest have reported differences that are statistically significant at stringent statistical thresholds (e.g., corrected for multiple comparisons; P , 0.05), suggesting that if such differences are present, they are probably small. At more liberal statistical thresholds, these studies provide evidence of disruptions in biologically plausible regions, including increases in several frontal regions, cerebellum (8), fusiform gyrus, and temporal pole (9) and decreases in subcallosal cortex and dorsal anterior cingulate cortex (10), as well as in pons, cerebellum, and precuneus (8). Investigating resting-state conditions using nuclear imaging with interregional correlations across subjects may be a more sensitive method to characterize abnormalities in SAD.…”
Section: Surrogates Of Neural Activity (Blood Flow Perfusion Metabomentioning
confidence: 87%
“…Finally, there is evidence that therapy results in altered glucose metabolism in the medial prefrontal cortex. In one experiment, after a course of tiagabine (a g-aminobutyric acid reuptake inhibitor), SAD participants exhibited increased regional metabolism in the ventromedial prefrontal cortex (10), whereas in another experiment, moclobemide therapy was associated with reductions in metabolism in medial dorsal prefrontal cortex (9).…”
Section: Surrogates Of Neural Activity (Blood Flow Perfusion Metabomentioning
confidence: 99%
“…We obtained similar results to these previous studies. However, the metabolism in the medial dorsal PFC decreased in patients with SAD after pharmacological treatment [52].…”
Section: Principal Findingsmentioning
confidence: 92%